2014
DOI: 10.1371/journal.pone.0099897
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Oxidative DNA Damage, Cell-Cycle Regulation and Neuronal Death May Influence the Clinical Manifestation of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is characterized by progressive cognitive decline associated with a featured neuropathology (neuritic plaques and neurofibrillary tangles). Several studies have implicated oxidative damage to DNA, DNA repair, and altered cell-cycle regulation in addition to cell death in AD post-mitotic neurons. However, there is a lack of studies that systematically assess those biological processes in patients with AD neuropathology but with no evidence of cognitive impairment. We evaluated markers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 106 publications
4
67
0
Order By: Relevance
“…NOX2 inhibition had no effect on the Mtran phenotype (CD16/32+/TGFb+), but it repolarized microglia/macrophages towards an M2-like phenotype, as demonstrated by significant increased expression TGFb (M2-like marker). In addition, we demonstrated that gp91ds-tat treatment significantly reduced H2AX protein expression in damaged cortex, a markers of oxidative stress-induced DNA damage, 25 at 7 days post-injury. Taken together, these data demonstrate that a delayed systemic intervention starting at 24 h post-injury that targets NOX2 activity in microglia/macrophages can alter M1-/M2-like balance in favor of the anti-inflammatory and neurorestorative M2-like phenotype, and this results in reduced oxidative damage in neurons at 7 days post-injury.…”
Section: Fig 7 (Continued)mentioning
confidence: 78%
“…NOX2 inhibition had no effect on the Mtran phenotype (CD16/32+/TGFb+), but it repolarized microglia/macrophages towards an M2-like phenotype, as demonstrated by significant increased expression TGFb (M2-like marker). In addition, we demonstrated that gp91ds-tat treatment significantly reduced H2AX protein expression in damaged cortex, a markers of oxidative stress-induced DNA damage, 25 at 7 days post-injury. Taken together, these data demonstrate that a delayed systemic intervention starting at 24 h post-injury that targets NOX2 activity in microglia/macrophages can alter M1-/M2-like balance in favor of the anti-inflammatory and neurorestorative M2-like phenotype, and this results in reduced oxidative damage in neurons at 7 days post-injury.…”
Section: Fig 7 (Continued)mentioning
confidence: 78%
“…In our data set we find lower levels of PRDX5 (–1.77 and −2.27 fold) at the PSD of NDAN versus AD which can potentially indicate decreased oxidative stress in the brains of these individuals [157]. PRDX5 can neutralize hydrogen peroxide, alkyl hydroperoxides and peroxynitrite [158, 159] and its expression is increased during oxidative stress [160].…”
Section: Discussionmentioning
confidence: 99%
“…Transcription of the highly GC-rich 5ʹ-UTR region of FMR1 promotes R-loop formation at that locus, and increases the propensity for R-loop formation in the CGG repeat and the size of these R-loops 127 . DNA damage triggers a DNA damage response (DDR), a series of signalling events that, if not corrected, leads to neuronal death 128,129 . Phosphorylated histone variant γH2AX, which is an important DDR signalling molecule that is involved in the recruitment of repair proteins to the site of the DNA lesion, has been detected in FXTAS inclusions 130 and in a neural cell model upon doxycycline-induced expression of expanded CGG repeat reporter RNA 131 .…”
Section: Molecular Pathogenesis Of Fxtasmentioning
confidence: 99%